Prognostic Implications of Lymph Node Status for Patients With Gallbladder Cancer: A Multi-Institutional Study - Amini, Neda (Ann Surg Oncol, 2016)
BACKGROUND: Although the American Joint Committee on Cancer (AJCC) classification is the most accepted lymph node (LN) staging system for gallbladder adenocarcinoma (GBA), other LN prognostic schemes have been proposed. This study sought to define the performance of the AJCC LN staging system relative to the number of metastatic LNs (NMLN), the log odds of metastatic LN (LODDS), and the LN ratio (LNR). METHODS: Patients who underwent curative-intent resection for GBA between 2000 and 2015 were identified from a multi-institutional database. The prognostic performance of various LN staging systems was compared by Harrell’s C and the Akaike information criterion (AIC). RESULTS: Altogether, 214 patients with a median age of 66.7 years (interquartile range [IQR] 56.5–73.1) were identified. A total of 1334 LNs were retrieved, with a median of 4 (IQR 2–8) LNs per patient. Patients with LN metastasis had an increased risk of death (hazard ratio [HR] 1.87; 95 % confidence interval [CI] 1.24–2.82; P = 0.003) and recurrence (HR 2.28; 95 % CI 1.37–3.80; P = 0.002). In the entire cohort, LNR, analyzed as either a continuous scale (C-index, 0.603; AIC, 803.5) or a discrete scale (C-index, 0.609; AIC, 802.2), provided better prognostic discrimination. Among the patients with four or more LNs examined, LODDS (C-index, 0.621; AIC, 363.8) had the best performance versus LNR (C-index, 0.615; AIC, 368.7), AJCC LN staging system (C-index, 0.601; AIC, 373.4), and NMLN (C-index, 0.613; AIC, 369.5). CONCLUSIONS: Both LODDS and LNR performed better than the AJCC LN staging system. Among the patients who had four or more LNs examined, LODDS performed better than LNR. Both LODDS and LNR should be incorporated into the AJCC LN staging system for GBA.